Pengaruh Keadilan Organisasi Terhadap Kinerja Pegawai : Peran Mediasi Organizational Citizenship Behavior - Surya Hamdani; Jufrizen Jufrizen (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2023)
The purpose of this research to analyze the effect of organizational justice on employee performance. Analyzing the effect of organizational citizenship behavior on employee performance, analyzing the mediating role of organizational citizenship behavior on the effect of distributive justice on employee performance and analyzing the mediating role of organizational citizenship behavior on the effect of procedural justice on employee performance at the Center for the Development of Quality Assurance for Vocational Education in the Field of Building and Electrical Fields, Medan. This type of research is associative. The approach used is associative and quantitative. So based on a population of 150 people, the sample taken is 122 people. Data collection techniques in this study were interviews, questionnaires. This data will be analyzed with a quantitative approach using statistical analysis, namely the partial least square - structural inquiry model (PLS- SEM). The results showed that Distributive Justice had a positive but not significant effect on Organizational Citizenship Behavior. Procedural Justice has a positive and significant effect on Organizational Citizenship Behavior. Distributive Justice has a positive and significant effect on employee performance. Procedural Justice has a positive and significant effect on employee performance. Organizational Citizenship Behavior has a positive and significant effect on employee performance. Organizational Citizenship Behavior cannot mediate or mediate the effect of Distributive Justice on Employee Performance. Organizational Citizenship Behavior mediates or mediates the effect of Procedural Justice on Employee Performance.